Impossible Space: Socio-Cultural Aspects Behind the Failure of THM Localization in Makassar City - Ahmadin (Research Agency for Humanity and Urban, 2023)
Localization of Nightlife Places or in Indonesian it is called THM was once a hot discourse discussed in public spaces in Makassar City, especially in 2005. This discourse went wild since a daily newspaper in this city published news about the approval of Makassar City DPRD members and several other members of the commission for coming up with this idea. Some of the reasons that support the idea that is still playing out at this level of discourse, are covered by the postulates of urban planning and order. Another reason is related to the development of the Makassar City tourism sector. This paper examines the socio-cultural problems that have caused this localization policy discourse to not be realized. Socio-culturally, the act of localizing THM is seen as an effort to facilitate immoral activities, whereas on the other hand, the local population is a community of adherents and adherents of siri' values. In fact, this discourse coincided with the rise of the movement for the enforcement of Islamic Sharia in South Sulawesi.